HARUT DAN MARUT DALAM TAFSIR MODERN (Studi Komparasi Penafsiran Sayyid Qutub dan Wahbah Zuhaili) - Mubarok, Ghozi; Jannah, Febriyatul (Reflektika, 2019)
HÄrÅ«t and MÄrÅ«t are phenomenal examples or historical figures. From it arises several issues whether they are elements of humans or angels until their purpose is passed down to earth, with the existence of magic capable of divorcing husband and wife relationships. This paper focuses on: Who are HÄrÅ«t and MÄrÅ«t according to Sayyid Qutub and Wahbah al-Zuhaili and The methods used in the study use a descriptive qualitative approach, while the data collection technique uses library techniques by understanding books, articles that match the title of this study. According to Sayyid Qutb's interpretation that HÄrÅ«t and MÄrÅ«t were angels sent down by God as tests and trials for humans at that time. HÄrÅ«t and MÄrÅ«t said to be of the angelic element is based on the understanding that the word malacain, pronounced fathah, thus carries the influence of the interpretation that both are indeed elements of angels. Meanwhile, according to Wahbah al-Zuhaili's interpretation, that HÄrÅ«t and MÄrÅ«t are human beings, arguing and saying that lafadh al-malakain is a majaz/parable for one who is considered noble, because of obedience and good nature, so that it is considered an angel. Magic cannot be separated from the role of HÄrÅ«t and MÄrÅ«t teaching to humans. Both are distinguishing and explanatory that the prophet Solomon did not obtain his power and prophethood by magic, but was purely a gift from God in the form of a miracle.